Expectancy Violation in Nonverbal Communication and Its Influence on Lecturer Perceptions in the Educational Space - Setiawaty, Puji Wahyu; Dollah, Syarifuddin (ELT Worldwide: Journal of English Language Teaching, 2025)
Student attire serves as a powerful form of nonverbal communication within the educational space, subtly shaping how students are perceived by academic staff. This study examines how university lecturers in Indonesia evaluate student dress across disciplinary boundaries, particularly comparing English-education compared to other study programme, as well as lecturers' perceptions of the relationship between student clothing and professionalism. Using a cross-sectional ex post facto survey design, data were collected from 13 lecturers at a public university through the validated 18-item Expectancy–Appearance Survey (EAS). Quantitative analysis revealed that the majority of lecturers have certain expectations regarding student appearance, especially in terms of neatness, politeness, and cleanliness, which are considered to support the academic atmosphere in the classroom. There is a tendency for lecturers to appreciate students who dress neatly and formally, because it is considered to reflect respect for the academic environment and interaction ethics, even though lecturers basically still provide the best learning to all students. As part of nonverbal communication, students are expected to pay more attention to their appearance while in class as a reflection of professionalism and academic culture. These findings sheds light on the norms surrounding nonverbal communication through appearance are not universally held but are shaped by disciplinary identity and generational factors. The study contributes to the literature on expectancy-violation theory in higher education and offers practical recommendations for more inclusive, context-sensitive dress guidelines. Recognizing and addressing these implicit appearance norms can promote equitable academic environments where professionalism is not misjudged through unspoken visual codes.